Violin Instructors’ Views On The Use Of Metaphors In Violin Lessons And The Metaphors They Use (Proceeding of the International Conference on Arts and Humanities, 2021)
This research aimed at finding out violin instructors’ views regarding the use of metaphors for teaching to play the violin and the metaphors they use in their lessons. It was carried out with 10 university instructors who teach lessons of violin. Data were collected by using a structured interview form consisting of 18 questions. Collected data were analyzed with descriptive analysis method. It was found out that the instructors reported using metaphors during teaching of the violin and they found it helpful to do so. Furthermore, the metaphors they use were listed for the manner of holding the violin and bow, legato, martele, spiccato, pizzicato, flageolet, trillo, position shifting, vibrato, nuance, and the period, tone, measurement structure, speed and the form of a given work. However, no specific metaphors were reported for detache and staccato. Apart from these, one respondent mentioned metaphor for sautille and another used metaphor for articulation. In line with the results, it is recommended to utilize metaphors in teaching how to play the violin, to choose comprehensible ones for their students, to conduct experimental studies examining the effects of metaphors on performance in the context of violin education, and to research into the use of metaphors as part of teaching various other instruments.
Keywords: violin education; violin lesson; violin instructor; metaphor